DIGITAL LEARNING ANALYTICS: ENHANCING EDUCATIONAL ASSESSMENT STRATEGIES AND ANALYZING THEIR MULTIFACETED INFLUENCE ON STUDENT ACHIEVEMENT - Abdul Wahab Syakhrani; Didi Sudrajat; Fitria Meisarah; Kartika Puspandari; Yunita Sinaga (Adisam Publisher, 2023)
This study investigates the multifaceted influence of digital learning analytics on student achievement within educational settings. The rapid integration of technology in education has given rise to the widespread utilization of digital learning analytics, which has the potential to transform how educational assessment strategies are designed and implemented. The study employs a mixed-methods approach, gathering quantitative data through surveys from various educators, students, and administrators while conducting qualitative interviews to provide deeper context. The findings indicate a significant adoption rate of digital learning analytics, with approximately 75% of surveyed institutions incorporating these tools into their assessment practices. Furthermore, most educators, administrators, and students perceive the positive impact of digital learning analytics on student achievement. However, the study reveals the nuanced effectiveness of various analytics tools and highlights pedagogical and ethical considerations associated with their use. The results underscore the need for tailored approaches to digital tool implementation and suggest the importance of balancing technological innovation with a holistic view of education. This research contributes to the ongoing dialogue on technology's role in education. It serves as a foundational step in understanding how digital learning analytics can enhance educational assessment and ultimately improve student achievement in the digital age.